2013
DOI: 10.1002/prot.24264
|View full text |Cite
|
Sign up to set email alerts
|

Computationally‐predicted CB1 cannabinoid receptor mutants show distinct patterns of salt‐bridges that correlate with their level of constitutive activity reflected in G protein coupling levels, thermal stability, and ligand binding

Abstract: The cannabinoid receptor 1 (CB1), a member of the class A G-protein-coupled receptor (GPCR) family, possesses an observable level of constitutive activity. Its activation mechanism, however, has yet to be elucidated. Previously we discovered dramatic changes in CB1 activity due to single mutations; T3.46A, which made the receptor inactive, and T3.46I and L3.43A, which made it essentially fully constitutively active. Our subsequent prediction of the structures of these mutant receptors indicated that these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 84 publications
3
38
1
Order By: Relevance
“…Indeed functional differences between agonists and inverse agonists (or antagonists) to GPCRs are well established. For example, recent studies show that single, double, and triple mutant forms of the CB1 receptor exhibit dramatic changes in function, switching from full inactivity to high constitutive activity and back for sequential mutations (26,27). (iv) The GEnSeMBLE approach for predicting the ensemble of thermally accessible protein-ligand complexes provides a tool for accurate GPCR-ligand predictions consistent with the GPCR pleiotropy paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed functional differences between agonists and inverse agonists (or antagonists) to GPCRs are well established. For example, recent studies show that single, double, and triple mutant forms of the CB1 receptor exhibit dramatic changes in function, switching from full inactivity to high constitutive activity and back for sequential mutations (26,27). (iv) The GEnSeMBLE approach for predicting the ensemble of thermally accessible protein-ligand complexes provides a tool for accurate GPCR-ligand predictions consistent with the GPCR pleiotropy paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CB1 (7,8), SuperBiHelix has been applied successfully to the adenosine A 3 receptor (16) and other adenosine receptors (22), serotonin 5-HT2B and 5-HT2C receptor (25), the histamine H3 receptor (26), the CCR5 receptor (27,28), TAS2R38 bitter taste receptor (29), and the V2 vasopressin receptor (30). The predicted GPCR structures in these studies were validated by predicting the binding sites and energies for known series of ligands and comparing with experimental mutagenesis, binding, and/or functional data.…”
Section: Discussionmentioning
confidence: 99%
“…The structures lead to an activation mechanism for CB1 that explains all experiments and that may play a role in other GPCRs. Additional mutants have also been designed and then tested in GTPγS assays (8), lending strong support to this activation mechanism.…”
Section: Validationmentioning
confidence: 96%
“…Accordingly, a number of studies have aimed to identify such regulatory motifs of CB 1 R. A detailed computational model based on the crystal structure of the b 2 -adrenergic receptor-Ga s complex, combined with mutational data, suggested that distinct residues in the ICL2 and ICL3 regions of the CB 1 R may be involved in the stabilization of the active, Ga i -coupled receptor conformation (Shim et al 2013). Two other recent studies have analyzed the role of several intramolecular salt-bridges, which may stabilize inactive, partially active, and fully active CB 1 R conformations (Ahn et al 2013b, Scott et al 2013. According to this model, D3.49 and R3.50 residues form salt-bridges with K4.41 and D6.30, respectively, which (together with a D2.63CK3.28 salt-bridge) may keep the receptor in a partially active conformation under basal conditions.…”
Section: Introductionmentioning
confidence: 99%